Legal regulation of criminal liability for crimes agains the environment - Savchuk, Olena; Butenko, Viktor (Archives of Criminology and Forensic Sciences, 2021)
The article analyzes the current legislation of Ukraine in the field of criminal liability crimes against the environment. The paper analyzes the current legislation of Ukraine in the field of criminal liability for crimes against the environment. Special attention is paid to the importance of enhancing criminal liability to ensure provided by the Constitution of Ukraine as a fundamental law and guarantor of constitutional rights and freedoms of a person and citizen, for the crimes against the environment and to compensate for the damage caused by the violation of this right. Research methods were general scientific and (dialectical, systematic), and special scientific methods. The use of dialectical method allowed to determine the general state and research prospects of issues on legal regulation of criminal liability for crimes against the environment. The systematic method was used in the process of studying the system of legislation in the outlined issue. Regarding the special method, the formal legal method was chosen, according to which the analysis of the current legislation of acts of Ukraine in the field of criminal liability for committing crimes in the field of the environment is carried out. Today, one of the global problems is climate change due to increasing industrial pollution (excessive concentration of environmentally hazardous industries, outdated and inefficient environmental equipment, unreliable technical systems and lack of qualified personnel in enterprises with high environmental risk), a significant number of vehicles, that do not meet environmental standards, and other factors that pollute the environment. All of these are significant threats to the global economy and international security due to increased direct and indirect risks related to energy security, food and drinking water supply, stable ecosystems, and risks to human health and life.